2006
DOI: 10.1002/aic.10804
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ceramic supports on microwave heating for composite dielectric food slabs

Abstract: A detailed theoretical analysis has been carried out to study efficient heating of one‐dimensional (1‐D) composite dielectric food slabs due to microwaves. Current study involves processing of beef with oil layers with/without ceramic support for various cases, such as the support and/or oil layer is directly exposed to microwaves (case 1), the beef layer is directly exposed to microwaves (case 2) and oil‐beef layers and the ceramic supports are exposed to microwaves at both the sides (case 3). A preliminary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Similar assumptions are also found in earlier literature [5][6][7][8][9][10][11]. The wave propagation due to uniform electric field, E x , obtained from Maxwell's equation is…”
Section: Microwave Propagation In Porous Multilayered Dielectric Withsupporting
confidence: 62%
See 1 more Smart Citation
“…Similar assumptions are also found in earlier literature [5][6][7][8][9][10][11]. The wave propagation due to uniform electric field, E x , obtained from Maxwell's equation is…”
Section: Microwave Propagation In Porous Multilayered Dielectric Withsupporting
confidence: 62%
“…A generalized heating strategy for materials due to uniform plane waves was derived. A theoretical analysis of microwave heating of food slabs supported by ceramic plates was also carried out by Basak and Meenakshi [11,12]. Their study involves processing of beef with oil layers with or without support for various cases.…”
Section: Introductionmentioning
confidence: 99%
“…111 Further investigations for other materials such as oil and beef samples reported that the supporting plate (ceramic and/ or metallic) may drastically alter the heating effects with a range of dielectric properties. 69,[112][113][114][115] It was observed that beef samples would exhibit greater thermal runaway especially with SiC plate in the presence of both sides distributed microwave incidence, whereas the oil samples would exhibit smaller thermal runaway effects with both sides equidistributed microwave incidence irrespective of any ceramic plates. 69,112 It was observed the average power absorption was enhanced for samples (beef-air and beef-oil) in presence of Al 2 O 3 support whereas the average power was smaller with SiC support for porous dielectric materials such as beef-air (b/a) and beef-oil (b/o).…”
Section: Microwave Heating Of Multiphase Systemsmentioning
confidence: 95%
“…Current study involves samples with/without supporting plate. Lateral dimensions (along x and y axes) are assumed to be very large compared to the total thickness of the sample (along z axis including ceramic layer) and similar modeling assumptions are also found in earlier literatures (Ayappa, Davis, Crapiste, et al, 1991;Ayappa et al, 1992;Basak & Meenakshi, 2006a, 2006bBasak & Priya, 2005). Based on the assumptions, one dimensional slab has been considered.…”
Section: Modeling and Simulationmentioning
confidence: 97%
“…Modeling on microwave heating of food samples is primarily governed by electromagnetic wave propagation which is based on two formulations: (1) Lambert's exponential law (Ayappa, Davis, Crapiste, et al, 1991;Barringer et al, 1995;Basak, 2004;Curet, Rouaud, & Boillereaux, 2008;Liu, Wang, & Sakai, 2005;Mao, Watanabe, & Sakai, 2005;Yang & Gunasekaran, 2004) and (2) Maxwell's equations (Ayappa, Davis, Crapiste, et al, 1991;Ayappa et al, 1992;Basak, 2004;Basak & Kumaran, 2005;Basak & Meenakshi, 2006a, 2006bBasak & Priya, 2005;Campanone & Zaritzky, 2005;Curet et al, 2008;Liu et al, 2005;Regier et al, 2001;Yang & Gunasekaran, 2004). Lambert's law is a simple power formulation which states that microwave power decays exponentially as a function of distance of penetration into the sample.…”
Section: Introductionmentioning
confidence: 99%